A gender perspective on the well-being of women during the climacteric - Marianela Fonseca Fernández; Laura Magda López Angulo (Medisur)
The climacteric constitutes a stage in a woman's life cycle characterized by biological, psychological and sexual symptoms of varying intensity that can worsen due to the overload generated by the multiple roles she plays in the family and society, and as a consequence affect her well-being. Starting from the fact that gender shapes the way in which the health problems of men and women are addressed, this article bases the importance of the gender perspective for the understanding and care of climacteric women, which will allow the development of comprehensive actions directed to promote their health and well-being.